Spectrophotometric, chromatographic and bioanalysis of selected recently approved drugs from 2015–2020 to treat cardiovascular diseases: an analytical review - Gharge, Shankar (2023)
Heart Study has been operating for more than 40 years, and throughout that time it has found a number of risk variables that interact negatively to have an overall negative effect on cardiovascular disease (CVD) with an estimated 17.9 million deaths per year, CVD is the world's leading cause of death.